Раритетний фітоценофонд України: структура та аналіз - Устименко, П.М.; Дубина, Д.В.; Вакаренко, Л.П. (Український ботанічний журнал, 2010)
Анализируется раритетный фитоценофонд, представленный в Зеленой книге Украины — первом официальном общенациональном государственном документе по охране растительных сообществ. Дается количественное распределение раритетных ассоциаций по типам растительности, приводится перечень формаций с наибольшим раритетным фитоценофондом каждого типа растительности. Характеризуется распространение раритетных ассоциаций в Украине, их фитоценотическая и ботанико-географическая значимость, представленность в природно-заповедном фонде. Дается краткий сравнительный анализ раритетного фитоценофонда. Рассмотрены задачи охраны растительности на современном этапе. An analysis of the rare phytocenotic stock (phytocenofund) represented in the Green Data Book of Ukraine (the first nationwide official governmental document on conservation of plant communities) is presented. Quantitative representation of rare associations by vegetation types is provided; the list of formations with the highest representation of the rare phytocenofund in each vegetation type is compiled. Distribution of rare associations in Ukraine, their phytotcenotic and phytogeographical significance, representation in nature conservation units are analyzed. A brief comparative analysis of the rare phytocenofund is given. Current tasks for conservation of vegetation are considered.